HOUSEHOLDS’ PERCEIVED CAUSES OF POVERTY IN SOUTHWEST NIGERIA - Joseph Omotoso AJAYI; Esan Agbabiaka ADERINOLA; Jimoh Atanda AFOLABI; Simeon Dada Yomi ALFRED; James Olaniyi OKUNLOLA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The Southwest geo-political zone of Nigeria is a blend of both educational advancement and abundant natural resource endowment. The region is rich in petroleum, bitumen, agricultural and forest resources. Despite the revenues from oil and other resources, poverty is very common among the citizens. The study was conducted to evaluate households’ perception of the causes of poverty in southwest Nigeria. The study made use of a multi-stage sampling technique to select two hundred and forty (240) respondents, who were household heads across two (2) southwest States of Ekiti and Ondo. Data for the study were collected with the aid of well-structured questionnaires administered on the household heads. Data collected were analysed using descriptive statistics. The analysis of households’ perception of the causes of poverty in southwest Nigeria indicated that corruption, weak institutions and poor governance was perceived “very high” cause of poverty in the study area with 51% of responses.